2008
DOI: 10.1007/s00439-008-0555-z
|View full text |Cite
|
Sign up to set email alerts
|

Apparent autosomal dominant keratoconus in a large Australian pedigree accounted for by digenic inheritance of two novel loci

Abstract: Keratoconus is a debilitating ocular disease characterised by progressive asymmetrical thinning of the cornea, the clear covering at the front of the eye. The resulting protrusion of the cornea results in severe refractive error, in the most severe cases requiring corneal grafting. It is a complex disease with a genetic component. Despite several reports of linked loci, major gene identification has been elusive. A genome-wide linkage scan in a large Australian pedigree with apparent autosomal dominant keratoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 24 publications
1
52
0
1
Order By: Relevance
“…[42][43][44] Genetics would also explain the apparent autosomal dominant pattern of inheritance found in certain families, the higher prevalence for the disease in families with one affected individual, and the high concordance among monozygotic twins. [45][46][47][48] Burdon et al 48 found a Mendelian inheritance pattern in an Australian family. On the other hand, consanguinity have been associated with a higher risk of development of keratoconus.…”
Section: Geneticsmentioning
confidence: 99%
“…[42][43][44] Genetics would also explain the apparent autosomal dominant pattern of inheritance found in certain families, the higher prevalence for the disease in families with one affected individual, and the high concordance among monozygotic twins. [45][46][47][48] Burdon et al 48 found a Mendelian inheritance pattern in an Australian family. On the other hand, consanguinity have been associated with a higher risk of development of keratoconus.…”
Section: Geneticsmentioning
confidence: 99%
“…32 Also digenic linkages have been reported in keratoconus, suggesting that more than 1 gene may contribute. 33 All these findings strongly suggest a genetic component to the development of keratoconus.…”
mentioning
confidence: 95%
“…Regarding the genetic etiology of keratoconus, even thought to be present, 11 is not fully understood. Some authors assume that the disease follows an autosomal dominant pattern of transmission in certain types of keratoconus, 12 and some candidate genes have already been identified. …”
Section: 9mentioning
confidence: 99%